Modern education quality requirements and information technologies in academic teachers' activities. (2016) - Noskova, Tatiana; Pavlova, Tatiana; Yakovleva, Olga; Smyrnova-Trybulska, Eugenia; Morze, Nataliia
This article analyses and compares the approaches and procedures of education quality evaluation at the universities participating in the IRNet project. Based on data obtained from a teachers' survey at three universities of Poland, Russia, and Ukraine, it is possible to formulate a set of internal and external factors, which influence the process of implementation of ICT and e-learning in educational activities. The aim of this article is to elaborate recommendations for the development of an educational institution policy in the field of e-learning and educational interactions management in the digital environment of a modern university.